Influence of various types of media and media platforms on the features of Chinese journalistic content - Luoxiao, Zhang (Journal of the Belarusian State University. Journalism, 2023)
The article presents the results of study of genre-thematic features, structure, tonality (modality) and specificity of the placement of journalistic content covering the events of the 24th Winter Olympic Games held in Beijing from 4 to 20 February 2022 in the socio-political, economic and sports media of China. It reveals the differences in the characteristics of the content of traditional and network media on various media platforms. The strategy of reflecting non-economic topics in a specialised economic and business publication is described.